In vitro and in vivo toxicity assessment of the senotherapeutic Peptide 14. (2022) - Zonari, Alessandra; Brace, Lear E.; Alencar-Silva, Thuany; Porto, William F.; Foyt, Daniel; Guiang, Mylieneth; Cruz, Edgar Andres Ochoa; Franco, Octavio L.; Oliveira, Carolina R.; Boroni, Mariana; Carvalho, Juliana L.
Abstract: Senotherapeutic molecules decrease cellular senescence burden, constituting promising approaches to combat the accumulation of senescent cells observed in chronological aging and age-related diseases. Numerous molecules have displayed senotherapeutic potential, but toxicity has been frequently observed. Recently, a new senotherapeutic compound, Peptide 14, was developed to modulate cellular senescence in the skin. In order to assess the potential toxic and genotoxic effects of the peptide, we observed the viability of human primary dermal fibroblasts and epidermal keratinocytes with Peptide 14 treatment, and show that it is mostly non-toxic in concentrations up to 100 μM. Cancer lines were also used to investigate its potential of modulating proliferation. Different concentrations of the peptide promoted a discrete reduction in the proliferation of cancerous cells of the MeWo and HeLa lineages. In full-thickness human skin equivalents, topically formulated Peptide 14 also failed to exert any significant irritation, nor cellular toxicity when added to the culture media. Genotoxic assays including the Ames, micronucleus, and karyotyping tests also indicate the safety of the peptide. Finally, the irritative potential of the peptide was assessed in human subjects in a repeated insult patch test executed using 1 mM peptide. No visible skin reactions were observed in any of the 54 participants. Taken together, the present data support that Peptide 14 is a senotherapeutic molecule with a positive safety profile as tested with cruelty-free models, justifying further studies involving the peptide. Graphical Abstract: ga1 Highlights: Senotherapeutics are promising actives for skin aging but may be toxic or irritating. Toxicity assessment of topical products can be executed using cruelty-free experiments. The senotherapeutic Peptide 14 is non-toxic and non-genotoxic according to in vitro assays. Peptide 14 has a positive safety profile, according to the RIPT assay with 50 participants.